Mafia brotherhoods : organized crime, Italian style - Paoli, Letizia (New York ; Oxford : Oxford University Press, 2003)
Paoli provides a clinically accurate portrait of Mafia behaviour, motivations and structure. This interdisciplinary work of history, politics, economics and sociology, reveals in detail the true face of one of the world's most mythologized criminal organizations.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Mafia -- Italy -- Sicily -- History; Mafia -- United States -- History; 'Ndrangheta -- History